OCT-based diagnosis, management, and predictors of recurrent stent failure: a cohort study - Cioffi, Giacomo Maria; Lamelas, Pablo; Shenouda, Mariam; Halperin, Jamie; Goffredo, Francesca; McGrath, Brian Patrick; Vega Servin, Norman Said; Mehta, Shamir R.; Jolly, Sanjit S.; Schwalm, J. D.; Natarajan, Madhu K.; Valettas, Nicholas; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundStent failure (SF) is a complication of percutaneous coronary intervention (PCI).ObjectivesThis study aimed to assess the relationship of the optical coherence tomography (OCT) determined cause of SF with time since stent implantation, treatment, and outcome.MethodsThis retrospective study included patients who underwent an OCT evaluation for SF from January 2013 to July 2023. In-stent findings were evaluated on OCT including tissue proliferation, tissue type, underexpansion, thrombus, and multiple stent layers. The relationship between time to presentation, treatment, and outcome was assessed.ResultsOf the 309 patients who underwent an OCT-guided PCI for SF, tissue proliferation was present in 228 (74%) and absent in 81 (26%). Among patients with tissue proliferation, OCT commonly showed lipidic neointima (n = 122, 54%), thrombus (n = 81, 36%), and underexpansion (n = 71, 31%). In patients without tissue proliferation, OCT commonly identified underexpansion (n = 58, 72%), thrombus (n = 55, 68%), and uncovered struts (n = 37, 46%). The mean time to SF was 6.89 ± 5.88 years with tissue proliferation and 2.98 ± 3.75 years without (p < 0.001). Patients with tissue proliferation were more likely to be treated with repeat stenting (78% vs. 60%, p < 0.001). Lipidic neointimal tissue and >1 layer of stent were predictors of target SF recurrence during a median 3 years of follow-up.ConclusionIn a large series of OCT-guided treatments of SF, tissue proliferation was more common, occurred later after stent implantation, and was more likely to be treated with repeat stenting than no-tissue proliferation. Lipidic neointimal tissue and >1 layer of stent were significant predictors of target SF during follow-up.